Synthesis and electrooptical properties of side-chain polymethacrylates and polycomplexes containing azobenzene moieties with different length spacers - Savchenko, Irina (Publishing House of Lviv Polytechnic National University, 2014)
We propose new structures of metal-containing azopolymers with changeable electro-optical properties depending on different length spacers. The new monomers – 4-{4-[4-methacroyloxy)butoxy)phenyl] diazenyl benzoic acid, 4-{4-[4-(methacroyloxy)octyl) oxy]phenyl}diazenyl] benzoic acid and their complexes with Co and polymers based on these ones were synthesized. The influence of the electric field on the absorption spectra of new metal-containing azopolymers was investigated. Electro-optical properties of polymeric films are determined by the re-orientation of dipole moments of azobenzene groups photo induced by the polarized light in the electric field. Increase of structural flexibility due to the photo isomerization of azobenzene groups increases the electro-optical effect value. Запропоновані нові структури металовмісних азополімерів із змінними електрооптичними властивостями в залежності від різної довжини спейсера. Синтезовані нові мономери – 4-{4-[4-(метакроїлокси) бутокси)феніл)діазеніл бензойна кислота, 4-{4-[4-(метакроїлокси) октил)окси)феніл)діазеніл бензойна кислота, їх комплекси з кобальтом і полімери на їх основі. Досліджено вплив електричного поля на поглинання нових металовмісних азополімерів. Встановлено, що електро-оптичні властивості полімерних плівок визначаються переорієнтацією дипольних моментів азобензольних груп, які індуковані впливом поляризованого світла в електричному полі. Показано, що збільшення структурної гнучкості внаслідок фотоізомеризації азобензольних груп збільшує величину електрооптичного ефекту.
Синтез і електроптичні властивості поліметакрилатів і полікомплексів, які містять азобензольні замісники з різною довжиною спейсера в бічному ланцюгу
Keywords: electrooptics; azobenzene; metallopolymers; polycomplexes; photo isomerization; dipole moment електрооптика; азобензол; металополімери; полікомплекси; фотоізомеризація; дипольний момент